2012
DOI: 10.5402/2012/534290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt-Bromide-Iodine Thermal Water Inhalation on Functional and Biochemical Lung Parameters

Abstract: Background. Inhalation of thermal water has been used empirically in the treatment of chronic diseases of upper and lower respiratory tract. This study investigates biomarkers of effect in exhaled breath (nitric oxide (NO)) and in exhaled breath condensate (EBC) (hydrogen peroxide (H 2 O 2 ), anions, toxic heavy metals of tobacco smoke) for patients with lung diseases inhaling salt-bromide-iodine thermal water. Methods. This study enrolled two groups of patients, twenty with alveolar pulmonary diseases-pneumoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…They have a well-known therapeutic and preventive effect, stimulating the immune responses and the resistance of the respiratory tract to pathogenic microorganisms. This positive effect is generally based on the patients’ subjective sense of wellbeing, whereas is more difficult to quantify clinical improvements (Corradi et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a well-known therapeutic and preventive effect, stimulating the immune responses and the resistance of the respiratory tract to pathogenic microorganisms. This positive effect is generally based on the patients’ subjective sense of wellbeing, whereas is more difficult to quantify clinical improvements (Corradi et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mineral-rich water inhalations have been demonstrated to be effective in ameliorating the elastic properties of pulmonary interstitium, reducing inflammation, and stimulating the muco-ciliary function. One of the current hypotheses explaining the mechanism of action of inhalation treatments is that inhalations can replace or increase glutathione (GSH), reducing oxidative stress associated with inflammation in lung disorders and production of reactive oxygen species (ROS) (Corradi et al 2012). The heat applied to the whole body during the water immersions could have ulteriorly positive effects on the respiratory system modulating innate and acquired immune defences (Cohen 2020;Masiero et al 2020b;Maccarone et al 2021a;Maccarone et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral-rich water inhalations have been demonstrated to be effective in ameliorating the elastic properties of pulmonary interstitium, reducing in ammation and stimulating the muco-ciliary function. One of the current hypothesis explaining the mechanism of action of inhalation treatments is that inhalations can replace or increase glutathione (GSH), reducing oxidative stress associated with in ammation in lung disorders and production of Reactive Oxygen Species (ROS) (Corradi et al 2012) Combining all these bene cial effects, in the spa setting customized post-COVID programmes could be drawn, referring, as suggested by Antonelli et al [20], to already existing rehabilitative plans, such as those ones prescribed for work-related respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Crenotherapy in children has been shown also to be capable of signi cantly reducing the number of respiratory infections, nasal symptoms, and neutrophil count (Varricchio et al 2013) Radon-enriched inhalation therapy has been demonstrated to improve objective indicators of nasal functionality in allergic rhinitis and chronic rhinosinusitis, and to cause relief of pulmonary obstruction in asthma (Kesiktas et al 2011). In patients with air ow obstruction (FEV1/FVC < 0.7), the index FEV1/FVC (forced vital capacity) signi cantly increased after 12 days of inhalation treatments (Corradi et al 2012).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation